Pesticide Application and Food Safety Issue in Nepal - Koirala, P.; Dhakal, S.; Tamrakar, A. S. (Journal of Agriculture and Environment, 2009)
It has been increasing pest population including weeds, invasive species, insects and insect vectors and plant diseases, which lead to increase pesticides on crop production. Some of the pesticides also contribute to global warming and the depletion of the ozone layer. Pesticides are the potential health hazards which have drawn attention to everyone. The current practice adopted in pesticides control in Nepal appears not enough in line with food safety. This has created a promising threat in food safety and human health. In turn, global warming is also likely to increase pesticide use and degrade food safety situation. Necessary measures should be adopted to curb upcoming alarming situation in food safety. Key words: Food safety; Global warming; Pesticides; Nepal The Journal of Agriculture and Environment Vol:10, Jun.2009 Page: 128-132